2011
DOI: 10.1021/ja1095717
|View full text |Cite
|
Sign up to set email alerts
|

Nonstatistical Dynamics in Unlikely Places: [1,5] Hydrogen Migration in Chemically Activated Cyclopentadiene

Abstract: A molecular dynamics simulation reveals the occurrence of nonstatistical dynamical effects in the ring-opening and subsequent [1,5] H migration of bicyclo[2.1.0]pent-2-ene. The symptoms of the effects do not show up in the overall kinetics or product branching ratios of the reaction, which are well explained by a master-equation analysis, but in an oscillatory preference for migration of the two methylene hydrogens. It is predicted that these oscillations could have an observable effect on final product ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 57 publications
3
44
0
Order By: Relevance
“…Even when the branching of reaction paths does occur at a local PES minimum, classical molecular dynamics (MD) simulations have shown that one cannot rely on the validity of the statistical approximation for gas-phase reactions. 15,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] The Figure 1. Schematic depiction of a PES with a bifurcating reaction path.…”
Section: Changes In the Code Of Behaviormentioning
confidence: 99%
“…Even when the branching of reaction paths does occur at a local PES minimum, classical molecular dynamics (MD) simulations have shown that one cannot rely on the validity of the statistical approximation for gas-phase reactions. 15,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] The Figure 1. Schematic depiction of a PES with a bifurcating reaction path.…”
Section: Changes In the Code Of Behaviormentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] Alongside these observations, a growing number of studies have shown that the extent of vibrational excitation and its subsequent relaxation dynamics can actually impact reaction outcomes in solvents. [20][21][22] For example, there is good evidence that thermal reactions as well-known as alkene hydroboration have a Markovnikov/AntiMarkovnikov product ratio which is determined by the extent of nascent vibrational excitation in the short lived addition complex. 12,23 Recently, it has even been suggested that solute/solvent interactions which take place in the course of transient vibrational relaxation dynamics provide a route to enantioselective amplification.…”
Section: Introductionmentioning
confidence: 99%
“…There has been some contention over the best way to model the energy loss, but on the whole such models have been highly successful for gas-phase calculations, and have started to see use in condensed phases. 6,7,8,9 Importantly, the selectivity expected for propene in the absence of collisional cooling would be lower than experiment while the selectivity expected if INT (R = Me) cooled fully is higher than experiment. As a result, any model for the energy loss would necessarily be able to reproduce experiment with a fitted cooling parameter.…”
Section: Introductionmentioning
confidence: 83%